Reverse lactate threshold test accurately predicts maximal lactate steady state and 5 km performance in running - Wahl, P.; Manunzio, C.; Zwingmann, L.; van de Weyer, S.; Bloch, W. (Biology of Sport, 2021)
This study evaluated the accuracy of the reverse lactate threshold (RLT) and the onset of blood lactate accumulation (OBLA; 4 mmol·L-1) to determine the running speed at the maximal lactate steady state (MLSS) and 5 km running performance in a field test approach. Study 1: 16 participants performed an RLT test, and 2 or more constant-speed tests, lasting 30 minutes each, to determine running speed at the MLSS. Study 2: 23 participants performed an RLT test and a 5000 m all-out run as an indicator of performance. The RLT test consisted of an initial lactate-priming segment, in which running speed was increased stepwise up to ~5% above the estimated MLSS, followed by a reverse segment in which speed was decreased by 0.1 m·s-1 every 180 s. RLT was determined using the highest lactate equivalent ([La- ]/running speed) during the reverse segment. OBLA was determined during the priming segment and was set at a value of 4 mmol·L 1 . The mean difference in MLSS was +0.06 ± 0.05 m·s-1 for RLT, and +0.13 ± 0.23 m·s-1 for OBLA. OBLA showed a good concordance with the MLSS (ICC = 0.83), whereas RLT revealed excellent concordance with the MLSS with an ICC = 0.98. RLT showed a very high correlation with 5000 m speed (r = 0.97). The RLT exhibited exceptional agreement to MLSS and 5000 m running performance. Due to this high accuracy, especially concerning the small intraindividual differences, the RLT test may be superior to common threshold concepts. Further research is needed to evaluate its sensitivity during the training process.